Sally trombone: for brass quintet - Fillmore, Henry; Katz, Marco (My University, 1996)
Music score for 2 trumpets, horn (or baritone), trombone, and tuba; originally for trombone and band.
Keywords: ragtime music; brass quintets; arrangements